PELATIHAN PENGGUNAAN MAGIC SCHOOL AI SEBAGAI UPAYA AKSELERASI KEGIATAN PADA PLATFORM MERDEKA MENGAJAR (PMM) BAGI GURU-GURU DI SMAN UNGGUL ACEH TIMUR - Amalia, Rizki; Muliani, Fitra; Mawarni; Sari, Intan; Armanda, Fahmi; Saumi, Fazrina (Fakultas Teknik, Universitas Samudra, 2025)
The Merdeka Mengajar (PMM) Platform developed by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) is a forum for teachers to share, collaborate and develop teacher competencies in preparing optimal learning. However, it is unfortunate that teacher activities in accessing PMM are still far from what is expected. One of the reasons is because teachers' time to study and develop learning plans or media is very limited. Therefore, there needs to be a contribution from lecturers and students through community service activities to assist teachers. The purpose of this activity is to assist teachers in preparing administration and learning equipment by utilizing MagicSchool.ai. The results of the survey showed that a) 70.8% stated that participants strongly agreed that they were skilled at using MagicSchool AI; b) 66.7% stated that they strongly agreed that the activities had an impact and the team was directly involved in socialization and training; c) 70.8% strongly agreed that participants were satisfied and fully involved in PKM activities.